High-moisture extrusion cooking on soybean-wheat protein mixtures: Effect of sodium alginate/xanthan gum/maltodextrin on promoting a fibrous structure - Wang, Fengqiujie; Gao, Yang; Gu, Xuelian; Luan, Binyu; Zhu, Ying; Huang, Yuyang; Zhu, Xiuqing (Frontiers in Nutrition, 2023)
Pertaining to meat substitutes, high-moisture extrusion cooking (HMEC) is a crucial processing technique that efficiently transforms proteins and polysaccharides into fibrous structures. In this study, different additions (1%, 2%, 3%, 4% and 5%) of sodium alginate (SA), xanthan gum (XG) and maltodextrin (MD) were used in the preparation of organised protein products based on soybean protein and wheat protein under high moisture extrusion conditions. It was revealed that SA-4%, XG-2% and MD-2% significantly enhanced the structural and physical properties of the fibres. The polysaccharides increased the water distribution of extrudates by enhancing protein-water interactions through hydrogen bonding, with MD-2% having the strongest ability to trap free water. The mechanism by which the polysaccharides improved the fibrous structure of extrudates involved the reorganization of molten proteins from the die head region to the cooling region, formation of new molecular bonds and enhancement of thermal stability. XG-2% significantly increased the β-sheet structure in the molten region (48.9 ± 1.35%) and showed the best thermal stability. Overall, SA-4% was able to better maintain the molecular bonding transformation and strong water absorption, which stabilised the protein conformation and formed the highest fibrous degree (2.1 ± 0.03). This suggests that the properties of the three polysaccharides can be used as modifiers of high water extruded vegetable proteins to improve the extruded materiality and functional properties.